(untitled) (The Lumbini Journal of Business and Economics, 2022)
The "Lumbini Journal of Business and Economics (Special Issue), Vol. X, No. 1/2" is finally ready to cater to the needs of the current business and economic environment in Lumbini Banijya Campus. Although it may be delayed, the Department of Research and Development at LBC is committed to enhancing the quality of research in the region. This small step by LBC will add value to all researchers conducting their research work. We extend our heartfelt gratitude to all the contributors during the International Seminar on Redefining Management Education in Nepal. Their invaluable research papers and critical comments have brought life to this journal. The editorial team also thanks the President of the Campus Management Committee of LBC, Mr. Motilal Pandey, the Campus Chief, Prof. Dr. Tara Prasad Upadhyaya, and all the faculties, staff, and students of LBC for their supportive attitude in bringing this issue to its final form. The first issue of this volume contains a total of eight research papers, each with a different flavor, to meet the needs of the current business and economic environment in Nepal. The editorial team has spared no effort to ensure this issue is completely error-free. However, as the saying goes, "to err is human," so we welcome and appreciate any suggestions or corrections that could guide us in the right direction for the future. Lastly, we would like to express our gratitude to all the editorial board members for their immense support in bringing this issue to the hands of our readers. Editor-in-chief April, 2023